Financial Performance in Banking: Does Good Corporate Governance Play A Role? - Agus Endrianto Suseno; Bela Ayu Novitasari; Yunus Harjito (Universitas Tidar, 2025)
The objective of this study is to examine how sound corporate governance affects banks' financial performance. The variables of the board of commissioners, directors, audit committee, management ownership, and institutional ownership are used as stand-ins for good corporate governance (GCG). The study's population consists of 46 banking businesses that are listed on the Indonesia Stock Exchange between 2018 and 2022. The sample in this study was obtained using a purposive sampling method, so that 215 data points were obtained from 46 banking companies. The technique used in this study is multiple linear regression using SPSS 21. The findings demonstrated that GCG had no discernible impact on banks' financial performance as measured by the factors of the board of commissioners, directors, audit committee, and management ownership. Furthermore, this study showed that good corporate governance, proxied by institutional ownership variables, proved to have a significant negative role in banking financial performance. This suggests that although institutional ownership is often considered a pillar of GCG, very large institutional ownership may create agency problems or focus on short-term gains to the detriment of long-term performance.